Afera taśmowa z 2014 roku jako przykład politycznego podziału w mediach – studium przypadku - Popielec, Dominika (Polityka i Społeczeństwo, 2020)
The aim of the article was to present the attitude of the media in Poland towards the outbreak of one of the most notorious political scandals of recent years. The subject matter of the analysis was the following: politicians’ positions against the disclosed „Tape Scandal” presented via the media; the attitude of the Polish media towards this political scandal and the „heroes” of this affair; evaluation of the weekly Wprost’s activity. The following research methods were used in the study: analysis of the content of selected media reports focusing on „Tape Scandal”, comparative method and case study. As a result of the analysis of the content of the weekly press, it was verified that the „Tape Scandal” of 2014 caused a political division in the media.